2022
DOI: 10.1101/2022.02.27.22271328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-acute symptoms, new onset diagnoses and health problems 6 to 12 months after SARS-CoV-2 infection: a nationwide questionnaire study in the adult Danish population

Abstract: Background. A considerable number of individuals infected with SARS-CoV-2 continue to experience symptoms after the acute phase. More information on duration and prevalence of these symptoms in non-hospitalized populations is needed. Methods. We conducted a nationwide cross-sectional study including 152 880 individuals aged 15-years or older, consisting of RT-PCR confirmed SARS-CoV-2 cases between September 2020-April 2021 (N=61 002) and a corresponding test-negative control group (N=91 878). Data were collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Just recently, a nationwide cross-sectional study in the Danish population with over 60.000 SARS-CoV-2 positive persons and a SARS-CoV-2 negative control group revealed significant risk differences for anosmia, fatigue/exhaustion, dyspnea and reduced strengths in legs/arms. 6 Our data, which do not include control groups, are consistent with the findings of the Danish questionnaire study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Just recently, a nationwide cross-sectional study in the Danish population with over 60.000 SARS-CoV-2 positive persons and a SARS-CoV-2 negative control group revealed significant risk differences for anosmia, fatigue/exhaustion, dyspnea and reduced strengths in legs/arms. 6 Our data, which do not include control groups, are consistent with the findings of the Danish questionnaire study.…”
Section: Discussionsupporting
confidence: 89%
“…These symptoms may nevertheless be essential to understand the burden of post-COVID conditions. 6 In comparison to the work of Augustin et al with a prevalence of 35% for six months lasting symptoms, 7 in our cohort the prevalence of long-lasting symptoms after three months was at 47% of hospital employees, hence, being comparable. Augustin et al defined the occurrence of at least one long lasting symptom out of four (anosmia, ageusia, fatigue, shortness of breath) as post-COVID syndrome.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous work indicates that 10-40% of individuals report symptoms months after acute COVID-19, including those who were not hospitalized initially, although these estimates vary by population and definitions of cases and outcomes. 46,47 A subset of PCR test-positive individuals in Denmark who were contacted found that 53% reported symptoms 6-12 months after infection, 48 and 5% of respondents in a study conducted in South Korea reported they were receiving treatment for symptoms a median of 454 days after their COVID-19 diagnosis. 49 Several large studies conducted in the United States Veterans Health Administration health care system, ~90% of whom were men and more than 70% were White, found increased outpatient clinic visits after hospitalization for COVID-19 or a positive SARS-CoV-2 PCR test, as well as increased risk of myocardial infarction and stroke in the months after infection; these findings may not be generalizable to other populations.…”
Section: Discussionmentioning
confidence: 99%